UJI KELAYAKAN PENILAIAN PROYEK BERBASIS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS ABAD 21 MAHASISWA PADA MATA KULIAH METODOLOGI PENELITIAN - Siregar, Rabiyatul Adawiyah; Lubis, Armansyah; Siregar, Ali Akbar; Daulay, Sattar; Siregar, Nurhijriyah Kam (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2022)
Research methodology is a required subject that must be taken by IPTS students in order to conduct their thesis guidance. It requires students to raise an education problem to carry out the introduction of research proposal and implementation. And so the students need to think critically. Basically, students have been difficulties to formulate problems that can be raised as a research. This requires a scientific or known as a saintifical approach and project assesment in order to students can be trained to work out proposals and research reports systematically using the scientific method. The use of a scientific-based project assessment instrument aimed ata valid . saintifical approach assesment of projects increasing 21st students’ critical thinking skills in research methodology courses. The use of this asssment instrument can be used for further decision-making in depelovment of future study processes of vresearch methodology. It is continuously carried out, therefore, makes a continual improvement-process. The method of research used development research with an addie model. The result of this study indicate that the assessment of the proscience-based project developed have been declared valid to increase student critical thought capability of 21st –century students on research methodology courses at IPTS.